Pengaruh Driver Stress terhadap Aggressive Driving pada Pengendara Motor di Kota Bekasi - Putri Anggraini; Budi Sarasati; Timorora Sandha Perdhana (Cahaya Ilmu Bangsa Institute, 2025)
Accidents are a phenomenon that often occurs on traffic roads. The number of accidents always increases every year from 2020 to 2023. This increase in the number of accidents occurs because the human factor is one of the factors that affect traffic accidents and is the dominating factor. This is because the density of traffic volume will make drivers behave more aggressively. Where aggressive driving behavior can cause traffic accidents. The purpose of this study is to determine whether there is an effect of driver stress on aggressive driving in motorcyclists. This study uses a quantitative approach with a simple linear regression method. The result of this study is that the effect of driver stress on aggressive driving is 18% and the rest is influenced by other factors not examined in this study. So it can be said that the hypothesis is accepted, namely the influence of driver stress on aggressive driving on motorcyclists in Bekasi City.